AIDS in Indonesia: Current Problems, Future Impacts and Challenges - Muzief Munir; Jasrizal Ilyas; Nyoman Suesen; Harmon Mawardi; Widagdo Widagdo (Paediatrica Indonesiana, 1997)
Since the First cases of AIDS were reported in the USA in 1981 and in Indonesia in 1987, millions of people throughout the world have been contracting this threateningly fatal disease. This report discusses and highlights the current problems and the future impacts of the disease in Indonesia. Data were collected from the Sub-Directorate STDs Control of the Directorate of Communicable Disease Control, Department of Health. The majority of cases were sexually active men and women between the ages of 15-49 years with the peak between 30-39 years in AIDS, and between 20-29 years in HIV(+), The mean age of HIV(+) males and remales was staÂtistically different (p<0.0002), where the mean age of HIV(+) males was 29.5 years, while in females it was 24.7 years. This new fatal disease has been reported from 15 out of 27 provinces in Indonesia, mainly from Jakarta, Bali, Riau, East Java and West Irian. Due to inadequate knowledge, and a limited surveillance of AIDS in Indonesia, no child was reported as having HIV(+)/AIDS.